HUBUNGAN ORANG TUA DAN ANAK (KAJIAN AL-QURAN SURAT AL-ISRA’ AYAT 23-24) - Muhammad Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Al-Qur'an as a guideline for human life has regulated all sides of life for the better, including the relationship between parents and children. Even so, the relationship between parents and children still occurs a lot of disputes and neglect of parents when they are old. Through this study the researcher examines the attitudes, behavior and relationships of children and parents in Al Isra verses 23-24 from the perspective of the interpretations of Al-Maraghi and Al-Azhar. This research has a library research style. With the main source of Al-Qur'an letter Al Isra verses 23-24, interpretations of Al-Maraghi and Al-Azhar and some other literature. The results show that: 1) Attitudes and behavior of children towards parents. The two mufassirs agreed that it is obligatory to care for and bear all the needs of parents when they are old, on the other hand the two mufassirs give an illustration of behavior that is not permissible including; a) Annoyed, b) Annoying, c) Speak harshly, d) Be arrogant. 2) The relationship between children and parents based on studies from two mufassir explained that, family ties will not be broken under any circumstances and situations, therefore a household for a child is not to run away from responsibility to parents. Hamka explained that the relationship and good behavior of children towards their parents without verses 23-24 even in human values it is obligatory for children to establish good relations and treat them as their parents treat them from birth to adulthood.